2021
DOI: 10.1186/s13017-021-00380-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute abdomen in the immunocompromised patient: WSES, SIS-E, WSIS, AAST, and GAIS guidelines

Abstract: Immunocompromised patients are a heterogeneous and diffuse category frequently presenting to the emergency department with acute surgical diseases. Diagnosis and treatment in immunocompromised patients are often complex and must be multidisciplinary. Misdiagnosis of an acute surgical disease may be followed by increased morbidity and mortality. Delayed diagnosis and treatment of surgical disease occur; these patients may seek medical assistance late because their symptoms are often ambiguous. Also, they develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 170 publications
(191 reference statements)
1
18
0
1
Order By: Relevance
“…In our series, wherein all cases showed radiological signs of NE, the mortality related to the condition occurred in 16% of all patients (27 of 171). This gure was much better than those reported by others, wherein mortality in patients with US or CT scan positive for suggestive signs of neutropenic enteritis or typhlitis reached 29.5% [24]. The mortality rate in the conservative arm was 10% (24 of 138), and among those who failed conservative management and were then referred to surgery, the mortality was 39% (13 of 33).…”
Section: Resultsmentioning
confidence: 58%
“…In our series, wherein all cases showed radiological signs of NE, the mortality related to the condition occurred in 16% of all patients (27 of 171). This gure was much better than those reported by others, wherein mortality in patients with US or CT scan positive for suggestive signs of neutropenic enteritis or typhlitis reached 29.5% [24]. The mortality rate in the conservative arm was 10% (24 of 138), and among those who failed conservative management and were then referred to surgery, the mortality was 39% (13 of 33).…”
Section: Resultsmentioning
confidence: 58%
“…A few studies have indicated that nonoperative management of uncomplicated diverticulitis in the immunocompromised may be safe and effective, even for recurrences [26,27]. Even though, similar failure rates of nonoperative treatment in acute sigmoid diverticular disease with equally severe disease distribution have been shown in patients with chemotherapy by Samdani et al [19], nonoperative treatment in IMS in the first episode of diverticulitis with abscess formation remains unclear and should be individualised [7,8,18,[28][29][30].…”
Section: Discussion and Con Clus Ionsmentioning
confidence: 99%
“…Patients with immunocompromise, including those with HIV infection, solid organ transplant, and malignancy, may have a reduced inflammatory response, which can lead to atypical and delayed presentations 6. These patients have a higher risk of poor outcomes related to intra-abdominal infection 7.…”
Section: Discussionmentioning
confidence: 99%